ICT-supported communication of scientists and teaching staff at the Faculty of Humanities and Social Sciences in Zagreb - Vrana, Radovan (2010)
Information and communication technology (ICT) has a great influence on the global system of scientific communication. The existing system is changing towards a new communication paradigm based on the exchange of scientific information in electronic information environment. Scientists are already experiencing changes in the ways they create, find, share, process, store and use scientific information. This paper will present results from the research among scientists and teaching staff at the Faculty of Humanities and Social Sciences in Zagreb (Croatia), regarding changes they experienced during the use of ICT in scientific communication.
Projekt MZOS
ENG